Vocal cord inflammatory myofibroblastic tumor with mucoid deposits harboring TIMP3-ALK fusion: A potential diagnostic pitfall - Yorita, Kenji; Togashi, Yuki; Nakagawa, Hideyuki; Miyazaki, Katsushi; Sakata, Seiji; Baba, Satoko; Takeuchi, Kengo; Hayashi, Yoshihiro; Murakami, Ichiro; Kuroda, Naoto; Oda, Yoshinao; Kohashi, Kenichi; et al. (Pathology international, 2019)
A 35-year-old Japanese man who had experienced hoarseness for 10 years presented with a vocal cord lesion. A gross examination revealed a left vocal cord polyp occupying two-thirds of the vocal space. The endoscopically resected lesion contained scattered atypical fibroblastic, stellate, or ganglion-like cells with mucoid stroma. Vacuolated cells were also seen. Lymphoplasmacytic infiltrate was largely undetectable. A vocal cord polyp was first suspected, but well-differentiated liposarcoma and inflammatory myofibroblastic tumor (IMT) were included in the differential diagnoses. The tumor cells were positive for anaplastic lymphoma kinase (ALK), calponin, and vimentin, and negative for other smooth muscle markers by immunohistochemistry. Structures resembling myofibroblasts were not observed by electron microscopy, which confirmed abundant rough endoplasmic reticulum in the tumor cells and accumulated lipid droplets in some tumor cells. ALK gene rearrangement was detected by fluorescence in situ hybridization, and TIMP3-ALK fusion was confirmed by 5' rapid ampliﬁcation of cDNA ends. We diagnosed the lesion as an IMT, and an ALK-rearranged stellate cell tumor may be postulated. This is the first report of a fusion partner gene of ALK in a case of laryngeal IMT.
Keywords: vocal cord polyp; liposarcoma; Humans; inflammatory myofibroblastic tumor; plazmocelulární granulom; hlasové řasy; Biomarkers, Tumor; dospělí; lidé; anaplastic lymphoma kinase; tyrosinkinasové receptory; myofibroblasty; nádorové biomarkery; Vocal Cords; Adult; Anaplastic Lymphoma Kinase; Granuloma, Plasma Cell; Male; tkáňový inhibitor metaloproteinasy 3; Receptor Protein-Tyrosine Kinases; anaplastická lymfomová kináza; Myofibroblasts; mužské pohlaví; Tissue Inhibitor of Metalloproteinase-3